Backus-Naur Form Based Script Definition Language for Multimedia Presentation Document - Teuku Marzuki Yacob, Maya Silvi Lydia (2001)
The integration of the text, graphic, audio, video and animation on the desktop promises to fundamentally challenge the old models of the printed document as the basis for information exchange. A multimedia document is a specification activity that can be used to coordinate the presentation runtime of the media objects. Several language that support the multimedia document exist today, for example HTML (HyperText Markup Language) and SMIL (Synchronized Multimedia Interaction Language). HTML is an SGML (Standard Generalized Markup Language) based standard document model that defines syntax to enrich text pages with structural and layout information. The dynamic modification to structure, layout and content of an HTML document are allowed using a scripting language which is known as DHTML (Dynamic HyperText Markup Language). SMIL is the web format for multimedia document, which is based on XML (extensible Markup Language). Driven by the use of the text markup tags in the multimedia document, the Script Definition Language or simply SDL is developed. The SDL is a definition language for multimedia document that provides a specification to include mulltimedia elements, such as text, image, animation, audio, and video. The structure of the SDL- is described using the Extended Backus-Naur Form (EBNF). In the EBNF, one way to determine the semantic of the language is achieved by derivation. The standard method to derive the semantic of the language in EBNF is using a parse tree. The multimedia document proposed is called the script document. There is a browser called the Script Multimedia Presentation (SMP) system, which is developed to generate the presentation output. The browser system scans the input file and produces error messages if it does not fulfill the specification. Each of the input documents derives a parse tree to show that the syntax follows the specification. Only the valid input document derives a valid parse tree and produces output. This can be concluded that the input document should strictly follow the SDL specification in order to generate the multimedia presentation.